DEVELOPING A BILINGUAL WEBSITE FOR CJDW CERAMICS & SOUVENIRS AS A LINK TO CONNECT TO THE MARKETPLACE AND SOCIAL MEDIA - Sofa Wahyu Ardhina (CV SWA Anugerah, 2024)
The researcher conducted this research using the Design and Development Research (DDR) method carried out by Richey and Klein. The researcher used the ADDIE model as a guide in developing material with several stages, namely analysis, design, development, implementation, and evaluation. The data collection methods used were interviews, surveys, and expert validation. At the analysis stage, it was found that CJDW Ceramics & Souvenirs had limited information and human resources in promoting their business online. The results of the questionnaire showed that the product must be easy to use, relevant, and can support several browsers in accessing it. At the design stage, the researcher designed the layout of the website and decided on the content presented on the website. At the development stage, the researcher made the content of the website and asked for validation from the expert when the product was ready to be validated. The experts used to consist of language experts and IT or website experts. At the implementation stage, the researcher also conducted field testing to improve the quality of the website and its content. The result of the expert validation process and field testing shows that the website is ready to use after going through several revisions. The final product is a bilingual website with five pages: Home, About, Products, Contact, and Others. This website offers detailed information in both Indonesian and English. By providing content in two languages, it aims to attract a broader range of visitors.